1893 Fla. Laws 52, §3 - (:unkn) unknown (My University, 1893)
Prohibited the manufacture, sale, or advertisement of any slung shot or metallic knuckles. Violators punished with imprisonment not exceeding three months, or fine not exceeding one hundred dollars, or both.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS